2014
DOI: 10.2989/17280583.2013.865627
|View full text |Cite
|
Sign up to set email alerts
|

The role of parental style in the conduct disorders: A comparison between adolescent boys with and without conduct disorder

Abstract: The study provided sufficient evidence to conclude that a specific style of parenting can contribute to the aetiology of conduct disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Assuming that these moral tendencies in sport reflect the youngsters' wider moral value system, this conclusion principally corroborates the premise that adolescents whose parents are authoritative are more prone to parental socialization and, therefore, more intensively internalize and apply their parents' social and moral values in various areas of their lives (Darling and Steinberg, 1993). Indeed, the current study's findings are consistent with previous findings suggesting that children and adolescents who were raised by authoritative parents might be more morally developed than those who were raised by non-authoritative parents (Freeze et al, 2014;Pinquart, 2017b;Fatima et al, 2020). Interestingly, the effects of parenting styles on moral and sport values discovered here did not interact with the athletes' sport type, which means that the differences between athletes from authoritative and non-authoritative families in these variables apply equally to both individual and team sports.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Assuming that these moral tendencies in sport reflect the youngsters' wider moral value system, this conclusion principally corroborates the premise that adolescents whose parents are authoritative are more prone to parental socialization and, therefore, more intensively internalize and apply their parents' social and moral values in various areas of their lives (Darling and Steinberg, 1993). Indeed, the current study's findings are consistent with previous findings suggesting that children and adolescents who were raised by authoritative parents might be more morally developed than those who were raised by non-authoritative parents (Freeze et al, 2014;Pinquart, 2017b;Fatima et al, 2020). Interestingly, the effects of parenting styles on moral and sport values discovered here did not interact with the athletes' sport type, which means that the differences between athletes from authoritative and non-authoritative families in these variables apply equally to both individual and team sports.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, as compared to an offspring from non-authoritative families, adolescents who were raised by authoritative parents exhibit several developmental socio-emotional advantages: they academically outperform their counterparts at school (Spera, 2005;Pinquart and Kauser, 2018), manifest better psychological adjustment in terms of lower depression and anxiety (Pinquart, 2017a;Yaffe, 2018a), tend to be more morally developed while engaging with less behavior and externalized problems (Freeze et al, 2014;Pinquart, 2017b;Fatima et al, 2020), have higher self-esteem (Pinquart and Gerke, 2019; more), and are more likely to be health behaviorally oriented (Vollmer and Mobley, 2013;Yaffe, 2018b). Accordingly, Darling and Steinberg (1993) submitted that since offspring of authoritative parents tend to endorse their parents' parental authority and feel obligated to obey their rules, they are more convenient for parental socialization and, consequently, tend to internalize more intensively their parents' social and moral values.…”
Section: Introductionmentioning
confidence: 99%
“…It was in fact essentially the mothers to recall and perceive their own fathers as over controlling but scarcely affective. Literature confirms this style of parenting to be associated with externalizing symptoms: parenting styles characterized mainly by strict discipline, high severity, limitation of autonomy, overprotection and rejection are associated with a variety of psychiatric disorders in adulthood, suggesting that these parenting practices can make the offspring vulnerable to externalizing psychopathology ( Rohner and Britner, 2002 ; Boričević Maršanić et al, 2014 ; Freeze et al, 2014 ; Sarajlić Vuković et al, 2015 ). In particular, Buschgens et al (2010) found in a sample of pre-adolescent who had experienced a lack of emotional warmth and a high overprotection by parents, that they were described by parents and teachers as more aggressive and prone to criminal acts, as well as more hyperactive.…”
Section: Discussionmentioning
confidence: 91%
“…Within the family environment adolescence is a crucial period for the development of disorders that can influence adult life too ( Reef et al, 2010 ; Nobile et al, 2013 ; Ormel et al, 2015 ). Research on parenting styles and psychosocial well-being conducted on the general population showed that a parent–adolescent relationship characterized by high levels of care and warmth is associated with minor levels of internalizing and externalizing problems in the offspring; conversely parental practices characterized by low care and high overprotection can make the offspring vulnerable to psychopathology ( Rohner and Britner, 2002 ; Andersson and Eisemann, 2003 ; Avagianou and Zafiropoulou, 2008 ; Boričević Maršanić et al, 2014 ; Freeze et al, 2014 ; Sarajlić Vuković et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the dimensions that are the focus of the present study, studies on parenting have also used other constructs to describe behavioral dimensions of parenting, such as neglectful or inconsistent parenting (e.g., Gardner, 1989; Tung & Lee, 2014) and overcontrolling or overprotective parenting (e.g., Freeze, Burke, & Vorster, 2014; Thomasgard & Metz, 1993), which all have shown to negatively affect child and adolescent development. Other studies have used a person-centered approach to describe parenting, instead of a variable-centered or dimensional approach, such as the authoritative, authoritarian, permissive, or disengaged typology (e.g., Lee, Daniels, & Kissinger, 2006; Luyckx et al, 2011; Mandara, 2003).…”
Section: Parenting Dimensions: From Three To Fivementioning
confidence: 99%